Are overweight and obesity risk factors for invasive mechanical ventilation in severe coronavirus disease 2019 pneumonia? - Maria Fernanda Coss-Rovirosa; Mercedes Aguilar-Soto; Dalia Cuenca; Mariana Velez-Pintado; Antonio Camiro-Zuñiga; Aldo Ferreira-Hermosillo; Moises Mercado (Archives of Endocrinology and Metabolism, 2021)
ABSTRACT Objective: Describe the demographic, clinical, and biochemical characteristics of overweight or obese people with severe COVID-19 pneumonia and evaluate its association with mechanical ventilation requirements in a Mexican cohort. Subjects and methods: Data were obtained from medical electronic records. Patients were divided in three groups according to the World Health Organization (WHO) classification of body mass index (BMI): lean, overweight and obese. Baseline characteristics and clinical course were compared among these 3 groups. Results: The study included a total of 355 patients with confirmed COVID-19 diagnoses. Patients with obesity and overweigh, according to the WHO classification, had no significantly increased risk of requiring intubation and invasive mechanical ventilation (IMV) compared to lean subjects, with an odds ratio (OR) of 1.82 (95% CI, 0.94-3.53). A post hoc and multivariate analysis using a BMI > 35 kg/m2 to define obesity revealed that subjects above this cut off had as significantly increased risk of requiring IMV after with an OR of 2.86 (95% CI, 1.09-7.05). Conclusion: We found no higher risk of requiring IMV in patients with overweight or obesity while using conventional BMI cutoffs. According to our sensitivity analyses, the risk of IMV increases in patients with a BMI over 35 kg/m2.